2019
DOI: 10.2166/ws.2019.084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PVP concentration on prepared PEI membranes for potential use on water treatment: effect of additive on membranes prepared for water treatment

Abstract: In this work, a series of polyetherimide (PEI) flat sheet membranes were produced with different concentrations of polyvinylpyrrolidone (PVP) addition via the phase inversion method. The effects of additions on membrane morphology and performance were investigated. Synthesized membrane had the properties of ultrafiltration membrane. Although PEI is not widely used for water treatment, in this study, the ferrous iron removal rate was investigated and good results were obtained. Through the membrane production e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to investigate the mechanical properties of the membranes under similar conditions to their operating environment [7]. The addition of PVP is also considered as it affects the membrane characteristics [47]. Tufekci et al have investigated the mechanical behaviour of PVP-added polyetherimide (PEI) membranes under uniform pressure using the finite element method, and they reported that the most mechanically favourable membrane is elliptical [48].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the mechanical properties of the membranes under similar conditions to their operating environment [7]. The addition of PVP is also considered as it affects the membrane characteristics [47]. Tufekci et al have investigated the mechanical behaviour of PVP-added polyetherimide (PEI) membranes under uniform pressure using the finite element method, and they reported that the most mechanically favourable membrane is elliptical [48].…”
Section: Introductionmentioning
confidence: 99%
“…Adding PVP into PAN provides checking over the properties of polymeric membranes, especially thermodynamically and kinetic-wise [ 16 , 17 ]. Addition of PVP causes thermodynamic instability and phase separation is to be observed [ 18 ]. Consequently, the blending of materials, which become soluble, is delayed and the polymer solution with a level of considerably significant viscosity goes through the process of phase separation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adding PVP into PAN provides checking over the properties of polymeric membranes, especially thermodynamically and kinetic-wise [16,17]. Addition of PVP causes a thermodynamic instability and a phase separation is to be observed [18]. So blending of materials, which become soluble, is delayed and the polymer solution with a level of considerably significant viscosity goes through the process of phase separation [19].…”
Section: Introductionmentioning
confidence: 99%